2015
DOI: 10.1097/aog.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Levator Ani Muscle Avulsion Injury After Forceps-Assisted and Vacuum-Assisted Vaginal Childbirth

Abstract: Objective Using three-dimensional transperineal ultrasound, we compared the prevalence of levator ani muscle injury after forceps with vacuum-assisted vaginal delivery. Methods This was a retrospective cohort study. Women who experienced at least one forceps delivery (across all deliveries) were compared to women who had at least one vacuum birth. On average, participants were 10 years from the index delivery. Three-dimensional transperineal ultrasound volumes were captured as cine loops at rest, with Valsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 20 publications
4
41
0
1
Order By: Relevance
“…The importance of this finding is due to the fact that instrumental vaginal delivery is an intervention that can be associated with maternal and neonatal morbidities, (10,12,13) such as pelvic floor injuries and fecal and urinary incontinence in the mother, (10,12) in addition to shoulder dystocia and facial nerve palsy in the neonate. (10,13) It is important to highlight that these instruments are handled only by qualified professionals, as this reduces the chances of injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of this finding is due to the fact that instrumental vaginal delivery is an intervention that can be associated with maternal and neonatal morbidities, (10,12,13) such as pelvic floor injuries and fecal and urinary incontinence in the mother, (10,12) in addition to shoulder dystocia and facial nerve palsy in the neonate. (10,13) It is important to highlight that these instruments are handled only by qualified professionals, as this reduces the chances of injury.…”
Section: Discussionmentioning
confidence: 99%
“…(10) In contrast, it has been associated with a higher risk of fetal morbidity and mortality, as well as maternal morbidities. (10,12,13) Laceration of the anal sphincter and of the birth canal, and displacement of the muscles of the pelvic floor are among maternal morbidities; (10,12,13) the neonatal morbidities are facial lesions, cephalo-hematomas, intracranial hemorrhage, ocular lesions, and fractures of the skull bones. (10) Obvious benefits are achieved by analgesia, despite the adverse conditions of its use.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of women delivered by operative vaginal birth, LAM avulsion observed on 3D transperineal ultrasound was associated with symptoms of prolapse (p=0.036) but not objective evidence of prolapse (p=0.20). 53 Others have found that objective evidence of prolapse is more common among those with levator ani muscle injury. 43 For example, among primiparous women 12 months after delivery, 54 levator avulsion was associated with objective and subjective measures of POP (OR 4.8, 95% CI 1.99–11.34).…”
Section: Phase Ii: Inciting Factors For Pelvic Floor Disordersmentioning
confidence: 99%
“…25 A recent meta-analysis described an odds ratio (OR) of 7.02 (5.04-9.78) comparing delivery with forceps with normal delivery. 26,28,29 It must be taken into account that some of the studies published to date 24,25,30,31 include a small sample size, so obtaining a clear conclusion regarding this association can be difficult. Although some authors report a higher rate of injuries associated with vacuum deliveries than with normal vaginal deliveries, 27 other researchers have not found significant differences.…”
Section: Introductionmentioning
confidence: 99%